Play robots to develop competences - Panelli, Erica; Guerrieri, Lorenzo; Bonarini, Andrea (Frontiers in Robotics and AI, 2025)
Play is a fundamental activity through which humans and animals acquire skills and competencies. Robots are increasingly capable of engaging in playful interactions with humans, offering new opportunities for learning, development, and social connection. Unlike traditional toys, robots possess autonomy and expressive capabilities, enabling them to propose actions, respond meaningfully, and exhibit intentions and emotions. This transforms the nature of play, making it more interactive and adaptive. For individuals with cognitive or physical impairments, robots can serve as predictable and engaging companions that attract attention, foster motivation, and facilitate social interaction in group settings. In this paper, we present a comprehensive framework to support the design of play-oriented robots and activities. Drawing on more than 20 years of research and development, we provide examples of low-cost robotic systems tailored for diverse user needs, including both typically developing individuals and those with disabilities. Through selected case studies, we demonstrate the effectiveness and versatility of our approach in supporting the design and analysis of playful experiences that are inclusive, goal-oriented, and developmentally beneficial.